Resolving the relationship between costume performance and body from the perspective of body philosophy - Xiaona Xie; Zhibin Ge (Trans/Form/Ação)
With the times’ progress and the growth of culture and art, the clothing industry has ushered in new development opportunities in the market. As its expansion and extension, clothing performance not only has high ornamental value, but also can exist independently as an art. However, in shaping the artistic image of clothing performance, the main focus is on the presentation of external images, lacking the expression of the rhythmic and connotative characteristics of body movements, which not only weakens the visual effect of the performance, but also has an impact on its integrity and continuity. Therefore, understanding the relationship between clothing performance and the body, and promoting their mutual integration and penetration are of great value and significance for the current development of visual art. Body philosophy is a philosophical discipline that explores the body and bodily experiences. It is concerned with the way the body perceives and exists. This can help performers and designers think about how clothing shapes and expresses personal and social identity, and how the diversity and change of identity can be explored through costume performance. In order to deeply study the relationship between clothing performance and body, and improve the effectiveness of clothing performance, this article explains the relationship between body and aesthetics based on the development history, function and value of clothing performance, combined with body philosophy theory. From the perspective of body philosophy, the body is an indispensable factor in costume performance, and costume performance can achieve artistic expression of the body, both of which interact and promote each other. In the development of aesthetic activities, the connection of the two closely has important value for achieving higher levels of visual representation.